1994
DOI: 10.1073/pnas.91.26.12765
|View full text |Cite
|
Sign up to set email alerts
|

Time course of Ca2+ concentration triggering exocytosis in neuroendocrine cells.

Abstract: We have used the secretory response of chromaffin cells to estimate the submembrane intracellular Ca2+ concentration ([Ca2+]1) "seen" by secretory granules during short depolarizations. The rate of secretion during a depolarization was assessed by combining the electrochemical method of amperometry and electrical capacitance measurements. The *To whom reprint requests should be addressed. 12765The publication costs of this article were defrayed in part by page charge payment. This article must therefore be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
142
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(149 citation statements)
references
References 30 publications
7
142
0
Order By: Relevance
“…It was shown that depolarization lasting between 2 and 40 ms support an increase in C m in rat melanotrophs (48). Dense-core vesicles that undergo depolarization-induced exocytosis require around 5 M Ca 2ϩ (49). The time constant of increase of the rapid C m component of around 30-40 ms (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that depolarization lasting between 2 and 40 ms support an increase in C m in rat melanotrophs (48). Dense-core vesicles that undergo depolarization-induced exocytosis require around 5 M Ca 2ϩ (49). The time constant of increase of the rapid C m component of around 30-40 ms (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Future indepth studies to address this question are warranted, perhaps, using a combination of patch-clamp, high-resolution Ca 2ϩ imaging and amperometry of vesicle-loaded oxidizable "false transmitters," similar to that described for other cells (Chow et al, 1994;Zhang and Zhou, 2002;Sakaba et al, 2005).…”
Section: Molecular Basis For the Inhibition By /Ea Of Capsaicin-triggmentioning
confidence: 99%
“…Neural secretion is a superlinear function of Ca 2ϩ concentration (30,31), implicating a possible synergism between sparks and Ca 2ϩ entry in controlling exocytosis. To appraise this possibility, we measured depolarization-induced vesicle secretion in the absence and presence of a RyR antagonist (whole-cell dialysis of 50 M ryanodine).…”
Section: Drg Sparks Directly Trigger Exocytosismentioning
confidence: 99%